2012
DOI: 10.1523/jneurosci.4185-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

The Head of the Table: Marking the “Front” of An Object Is Tightly Linked with Selection

Abstract: Objects in the world do not have a surface that can be objectively labeled the "front." We impose this designation on one surface of an object according to several cues, including which surface is associated with the most task-relevant information or the direction of motion of an object. However, when these cues are competing, weak, or absent, we can also flexibly assign one surface as the front. One possibility is that this assignment is guided by the location of the "spotlight" of selection, where the select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…This role for attention might also generalize to rotation in depth. Spatial selection can help pull the representation of a surface closer to the observer (Xu & Franconeri, 2012), and could play a similar role in 3D rotation.…”
Section: Discussionmentioning
confidence: 99%
“…This role for attention might also generalize to rotation in depth. Spatial selection can help pull the representation of a surface closer to the observer (Xu & Franconeri, 2012), and could play a similar role in 3D rotation.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that only one of the objects is selectively attended, such that the spotlight starts at, e.g., the green object, producing (green exists), and shifts to produce (red exists + just shifted left). In support of this idea that attention shifts are needed to perceive spatial relations between objects, we used an electrophysiological attention tracking technique to show that during such simple relational judgments, participants do shift their attention in systematic ways toward one of the objects (Franconeri et al, 2012 ; Xu and Franconeri, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous psychophysical studies have suggested a close association between apparent motion perception and attention by demonstrating a type of motion perception that does not need to be driven by low-level luminance contrast energy, is capacity limited, and is flexibly driven by an attended feature (Ashida, Seiffert, & Osaka, 2001; Cavanagh, 1992; Lu & Sperling, 1995). The present results show that the type of attention that mediates this flexible motion mechanism may be related to other complex abilities that rely on coordinating one or more spotlights of attentional selection (Cavanagh, 2004), such as object tracking (Drew, Horowitz, Wolfe, & Vogel, 2011) and visual structure representation (Xu & Franconeri, 2012), which are associated with similar shifts in contralateral negativity.…”
mentioning
confidence: 64%